N-cadherin induces partial differentiation of cholinergic presynaptic terminals in heterologous cultures of brainstem neurons and CHO cells - Flannery, Richard J.; Brusés, Juan L. (Frontiers in Synaptic Neuroscience, 2012)
N-cadherin is a calcium-sensitive cell adhesion molecule commonly expressed at synaptic junctions and contributes to formation and maturation of synaptic contacts. This study used heterologous cell cultures of brainstem cholinergic neurons and transfected Chinese Hamster Ovary (CHO) cells to examine whether N-cadherin is sufficient to induce differentiation of cholinergic presynaptic terminals. Brainstem nuclei isolated from transgenic mice expressing EGFP under the control of choline acetyltransferase transcriptional regulatory elements (ChATBACEGFP) were cultured as tissue explants for five days and cocultured with transfected CHO cells for an additional two days. Immunostaining for synaptic vesicle proteins SV2 and synapsin I revealed a 3-fold increase in the area of SV2 immunolabeling over N-cadherin expressing CHO cells, and this effect was enhanced by coexpression of p120-catenin. Synapsin I immunolabeling per axon length was also increased on N-cadherin expressing CHO cells but required coexpression of p120-catenin. To determine whether N-cadherin induces formation of neurotransmitter release sites, whole-cell voltage-clamp recordings of CHO cells expressing alpha-3 and beta-4 nicotinic acetylcholine receptor (nAChR) subunits in contact with cholinergic axons were used to monitor excitatory postsynaptic potentials (EPSPs) and miniature EPSPs (mEPSPs). EPSPs and mEPSPs were not detected in both, control and in N-cadherin expressing CHO cells in the absence or presence of tetrodotoxin. These results indicate that expression of N-cadherin in non-neuronal cells is sufficient to initiate differentiation of presynaptic cholinergic terminals by inducing accumulation of synaptic vesicles; however, development of readily detectable mature cholinergic release sites and/or clustering of postsynaptic nAChR may require expression of additional synaptogenic proteins.